The Washington review of strategic and intelligence studies - Georgetown University. Center for Strategic and International Studies. (Center for Strategic and International Studies, Georgetown University, 1978)
Cumulative indexes for 1978-1981 on microfiche.Continued by: Washington quarterly, ISSN 0163-660X.